How to reactivate the Alumni-UNICAMP Platform from the Alumni-UC Network - Godoy, Andréa Cristina Tavares Franco de (ICAReAlumni Conference Proceedings, 2023)
Objectives ●To present the outcomes from the international mobility to the University of Coimbra (UC) and experiences to identify actions that culminated in the high adherence of the Alumni UC ●To identify new paths in order to contact and attract the graduate back to UNICAMP ●To incorporate the knowledge acquired in order to publicize the platform and attract more IB graduates to Alumni